Antibacterial Activity of the Ethyl Acetate Fraction of Qust Al-Hindi (Saussurea lappa) in Inhibiting Escherichia coli Growth Using the Agar Diffusion Method - Mulya, Esti Lestari; Sukmawati, Sukmawati; Fitriana, Fitriana (Journal Microbiology Science, 2025)
The root of the Qust al Hindi plant (Saussurea lappa) has been recognized for its potential in treating infectious diseases. This research aims to evaluate the antibacterial activity of the ethyl acetate fraction of Qust al Hindi roots against digestive tract bacterial infections, specifically targeting Escherichia coli, using the agar diffusion method. The study commenced with an initial screening test at a concentration of 1%, followed by Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) tests at concentrations of 0.25%, 0.5%, 1%, 2%, 4%, 8%, and 16%. The MIC was determined to be 1%, while the MBC was observed at 8%. Further antibacterial activity testing was conducted at concentrations of 32%, 16%, and 8%, with the optimal activity noted at 32%